Tourism, amenities, and welfare in an urban setting - Gianandrea Lanzara; Gaetano Alfredo Minerva (Alma Mater Studiorum - Università di Bologna, Dipartimento di Scienze Economiche (DSE), 2018)
Using data on Italian cities, we document that, over the period 2001-2011, the number of establishments and employment in some key service industries are positively related to the inflow of tourists. We then build a general equilibrium model of small open cities to study the impact of tourism on endogenous amenities, factors' allocation across sectors, prices, and welfare. Tourism has two main effects on the urban economy: first, consistently with the observed pattern in the data, it increases the number of firms (an endogenous consumption amenity) and employment in the non-tradable sector; second, it increases prices. In the model tourism may hurt the resident population: with unequal land endowments, poorer residents are hurt by tourism because the rise in city prices offsets the positive impact on the urban consumption amenity. Along with several other extensions to the baseline model, we study the interplay of historical (exogenous) amenities, tourism and residents welfare in a system of two cities.
Keywords: R13; R31; R32; Z30; Z32; 330; City; Consumption Amenities; Real Estate; Tourism; Welfare